Peran Kegiatan Melipat Kertas untuk Mengembangkan Motorik Halus, Kreativitas dan Percaya Diri Siswa di TK A XYZ Jakarta - Anastasia Listiyani (Jurnal Syntax Admiration, 2024)
Fine motor skills, creativity, and confidence are important parts of early childhood development. This study aims to determine the role of paper folding in developing fine motor skills, creativity, and confidence of students of Kindergarten A XYZ Jakarta. The research was conducted by pretest and posttest. The subjects in the study totaled twenty-one students in one class. This type of research uses a quantitative experimental method with a pre-experimental design, in the form of one group pretest-posttest without a control class. The research instrument used is a rubric for all variables that have been validated by two experts. Data collection was carried out by observation. To process the data in the study, calculations were carried out by looking for n-gain to find out the pretest and posttest data and then tested using the Wilcoxon signed Rank Test. The results of the fine motor hypothesis test showed the acquisition of asymp. Sig. (2-tailed) = 0.000; The results of the creativity hypothesis test showed the acquisition of asymp. Sig. (2-tailed) = 0.000; And the results of the confident hypothesis test show the acquisition of Asymp. Sig. (2-tailed) = 0.000. It can be concluded that there are differences in fine motor, creativity, and confidence before and after paper folding activities in students at Kindergarten A XYZ Jakarta. So that by folding paper, students' fine motor skills, creativity and confidence can be developed.